2000
DOI: 10.1093/bja/85.3.465
|View full text |Cite
|
Sign up to set email alerts
|

Transcranial magnetic-evoked potentials under total intravenous anaesthesia and nitrous oxide

Abstract: Magnetic stimulation of the cortex and recording of the motor-evoked potentials (MEPs) by electromyography (EMG) is a well proven method to assess the descending pathways of the spinal cord and detect neurological impairment. We have assessed, in 33 adult patients undergoing spinal surgery, the influence of four total i.v. anaesthesia regimens (TIVA) on this recording technique. In 20 patients, the effect of 50% nitrous oxide was also studied. MEP amplitudes, latencies and success rates of stimulation were obt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(11 citation statements)
references
References 5 publications
0
11
0
Order By: Relevance
“…This is in line with the general notion that early evoked responses in the primary somatosensory region are often preserved during anesthesia, deep sleep, and vegetative state (Sloan et al, 1989; Alkire et al, 2008), when the association neocortex is deactivated (Laureys, 2005). A study of adult patients undergoing spinal surgery using transcranial magnetic stimulator reported that administration of midazolam had the least effect on motor-evoked potentials (Sihle-Wissel et al, 2000). Low-delta augmentation in the somatosensory-motor region might reflect the inhibition of the underlying cortical function as the result of sedation; low-delta activity during slow-wave sleep is generally associated with long-lasting neuronal hyperpolarization and cellular silence at the level of intracellular recording (Timofeev et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…This is in line with the general notion that early evoked responses in the primary somatosensory region are often preserved during anesthesia, deep sleep, and vegetative state (Sloan et al, 1989; Alkire et al, 2008), when the association neocortex is deactivated (Laureys, 2005). A study of adult patients undergoing spinal surgery using transcranial magnetic stimulator reported that administration of midazolam had the least effect on motor-evoked potentials (Sihle-Wissel et al, 2000). Low-delta augmentation in the somatosensory-motor region might reflect the inhibition of the underlying cortical function as the result of sedation; low-delta activity during slow-wave sleep is generally associated with long-lasting neuronal hyperpolarization and cellular silence at the level of intracellular recording (Timofeev et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…However, even among the intravenous anesthetics, there were differences with respect to the suppressive effect on MEP amplitude. MEP amplitudes were more profoundly depressed by propofol as compared to etomidate, although both drugs are thought to act mainly by activation of GABAARs (Sihle-Wissel et al, 2000). On the other hand, combining ketamine with propofol seemed to diminish the depressant effect of propofol (Sihle-Wissel et al, 2000).…”
Section: Effects Of Anesthetics and Analgesics On Tms-emg Measures Ofmentioning
confidence: 94%
“…MEP amplitudes were more profoundly depressed by propofol as compared to etomidate, although both drugs are thought to act mainly by activation of GABAARs (Sihle-Wissel et al, 2000). On the other hand, combining ketamine with propofol seemed to diminish the depressant effect of propofol (Sihle-Wissel et al, 2000). This might be explained by the fact that the intravenous anesthetic ketamine alone did not suppress MEP amplitude, but even led to MEP facilitation (Di Lazzaro et al, 2003).…”
Section: Effects Of Anesthetics and Analgesics On Tms-emg Measures Ofmentioning
confidence: 99%
“…[1][2][3][4] However, MEPs are not widely utilized in the operating room because they are considerably affected by general anesthesia, especially with volatile anesthetics, including halothane, enflurane, isoflurane, sevoflurane, and desflurane. [10][11][12][13] In contrast, modulations in the stimulation pattern alter MEPs. [10][11][12][13] In contrast, modulations in the stimulation pattern alter MEPs.…”
mentioning
confidence: 99%